2008
DOI: 10.1016/j.humpath.2007.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of: Stromogenic prostatic carcinoma pattern (carcinomas with reactive stromal grade 3) in needle biopsies predicts biochemical recurrence-free survival in patients after radical prostatectomy

Abstract: We previously reported that reactive stromal grading in radical prostatectomies is a predictor of recurrence and that reactive stromal grading 0 and 3 are associated with lower biochemical recurrence-free survival rates than reactive stromal grading 1 and 2. We explored the prognostic significance of reactive stromal grading in preoperative needle biopsies. At Baylor College of Medicine, 224 cases of prostatic carcinoma were diagnosed by needle biopsy. Reactive stromal grading was evaluated on hematoxylin-eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Clinical data have indicated that reactive stroma could be a predictor of biochemicalfree recurrence in PCa patients independent of Gleason score and other pathologic variables (45,46). A recent microarray study found that EGF transcripts increased significantly in laser-captured reactive prostatic stroma compared with that in matched normal stroma (47).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data have indicated that reactive stroma could be a predictor of biochemicalfree recurrence in PCa patients independent of Gleason score and other pathologic variables (45,46). A recent microarray study found that EGF transcripts increased significantly in laser-captured reactive prostatic stroma compared with that in matched normal stroma (47).…”
Section: Discussionmentioning
confidence: 99%
“…The fibers are irregular in length and thickness, and there is a delicate fibrillary background. 12,14,16 …”
Section: Definition Of Reactive Stroma In Pcamentioning
confidence: 99%
“…Reactive stroma in PCa was described in our previous studies and characterized at the phenotypic, [12][13][14][15] morphological, 16,17 and genomic levels. 18 We immunophenotyped RS as cells coexpressing vimentin and smooth muscle ␣-actin, with loss of terminal muscle differentiation markers such as desmin and/or calponin.…”
mentioning
confidence: 99%
“…[8]). Stroma abundance has been related to poor patient prognosis [922]. Intratumoural stroma has also been associated with chemotherapy resistance by fibroblast proteins inhibiting tumour cell apoptosis [23] or by reducing chemotherapy delivery [24].…”
Section: Introductionmentioning
confidence: 99%